Product improvement, sorption, isotherm and critical moisture content of dehydrated cavendish bananas (Musa cavendishi) - De Jesus, Rosario L.; De Leon, Sonia Y. (1983)
This study aimed at improving the characteristics of banana figs or dehydrated bananas (Musa cavendishii) and studying its storage characteristics. Under the conditions of the study, the best product obtained in terms of appearance, color, texture, and general acceptability was by immersing the table-ripe fruit in 1.0% sodium metabisulfite for 20 minutes and drying the whole fruit at 60-79°C (140-160°F) for a total of 26 hours. After two days, the product had a moisture content ranging from 20-25%, a sweet banana flavor, a color ranging from "golden yellow" to "go;den brown" and texture ranging from "firm and dry" to "tender and moist". The sorption isotherm and critical moisture content determined was done to know the storage characteristics of the product. The sorption isotherm was the typical sigmoidal shape. The calculated maximum allowable water vapor transmission rate (WVTR) based on an initial moisture content of 25.79% (dry basis) and a critical moisture content of 32.72% (dry basis) was 23.33 g/day/m2 at 81% relative humidity gradient and 28-30°C temperature. The packaging material selected which meets the WVTR requirements are low and medium density polyethylene.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Bananas, Dehydration of